Kualitas Pelayanan di Perseroan Terbatas Pegadaian (Persero) Cabang Palangkaraya - Sabirin Muhtar; Hini Fitriya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to determine the implementation and factors that become a barrier and supporter in the quality of service in the company's local pawnshop (Persero) Palangkaraya branch of central Kalimantan. The type of research used is qualitative research methods with descriptive analytical techniques. Researcher's position in qualitative research, the researcher is a planner, Data collector Executor, analysis, data interpreter and eventually, researchers become the reporter of the results of his research. The data source in this study is the employees of the company's limited pawnshop (Persero) Palangkaraya branch that serves customers and customers. Based on the results of the research can be explained that the service of the company's pawnshop (Persero) Palangkaraya Branch Central Kalimantan, a barrier factor encountered (1) the number of complaints from the customer about the timeliness that resulted in Quality of service to limited liability company. Pawnshop (Persero) Palangkaraya Branch still not quality. (2) Accuracy of service is not good, because there are still employees who are less thorough in the transaction to the customer. (3) Polite and friendly attitude given by the officers of the limited liability company (Persero) Palangkaraya branch to the community. (4) is still a lack of convenience in service so that customers feel complicated in dealing in the company of Pawnshop Limited (Persero) Palangkaraya branch. (5) Still lacks the support of existing facilities and infrastructures. (6) Still, the lack of participation in the community.